Galectin‐1 deletion in mice causes bone loss via impaired osteogenic differentiation potential of BMSCs. Issue 9 (25th August 2022) - Chen, Yu; Liu, Yanbin; Zhang, Yangyang; Yu, Jiangming; Tang, Liang
Abstract: Bone formation is dependent on the osteoblasts which are differentiated from bone marrow stromal cells (BMSCs). In addition to potent proliferation, self‐renewal, and pluripotent differentiation, BMSCs have been extensively studied due to their low immunogenicity and immunomodulatory effects. Recently, galectin‐1 (Gal‐1) has been proposed as a potent mediator of immunomodulatory properties of BMSCs. Previous study demonstrated that Gal‐1 showed age‐related decline in mice serum and serum Gal‐1 was positively associated with bone mass in mice. The current study makes attempts to elucidate the functional role of Gal‐1 in skeletal system by investigating the regulation of Gal‐1 expression during BMSCs osteogenic differentiation and the molecular mechanisms underlying the effects of Gal‐1 on BMSCs osteogenic differentiation. In Gal‐1 null (−/−) mice, bone loss was observed due to bone formation attenuation. In in vitro experiments, Gal‐1 supported the osteogenic differentiation of BMSCs by binding to CD146 to activate Lrp5 expression and Wnt/β‐catenin signaling pathway. Meanwhile, there was positive feedback regulation via Wnt/β‐catenin signaling to maintain Gal‐1 high‐level expression during osteogenic differentiation of BMSCs. More importantly, Gal‐1 down‐regulation in BMSCs and attenuation of osteogenic differentiation potential of BMSCs were observed in aged mice compared with young mice. Gal‐1 over‐expression could enhance osteogenic differentiation potential of aged BMSCs. Our study will benefit not only for deeper insights into the functional role of Gal‐1 but also for finding new targets to modulate BMSCs osteogenic differentiation.